Experimental and theoretical studies of the ancillary ligand (E)-2-((3-amino-pyridin-4-ylimino)-methyl)-4, 6-di-tert-butylphenol in the rhenium(i) core. (1st June 2015) - Carreño, Alexander; Gacitua, Manuel; Schott, Eduardo; Zarate, Ximena; Manriquez, Juan Manuel; Preite, Marcelo; Ladeira, Sonia; Castel, Annie; Pizarro, Nancy; Vega, Andrés; Chavez, Ivonne; Arratia-Perez, Ramiro
Abstract : The Re(CO)3 (deeb )L + complex with an ancillary ligand that presents electron withdrawing effects was synthesized and studied by experimental and computational methods. Abstract : The fac -[Re(CO)3 (deeb )L ] + complex (C2 ) whereL is the ( E )-2-((3-amino-pyridin-4-ylimino)-methyl)-4, 6-di- tert -butylphenol ancillary ligand, which presents an intramolecular hydrogen bond, has been synthesized and characterized using UV-vis, 1 H-NMR, FT-IR, cyclic voltammetry and DFT calculations. The UV-vis absorption and emission properties have been studied at room temperature and the results were compared with TDDFT calculations including spin–orbit effects. We report an alternative synthesis route for the fac -Re(CO)3 (deeb )Br (C1 ) complex wheredeeb = (4, 4′-diethanoate)-2, 2′-bpy. Besides, we have found that theC1 shows a red shift in the emission spectrum due to the nature of the ancillary electron donating ligand, while theC2 complex shows a blue shift in the emission spectrum suggesting that the ancillary ligandL has electron withdrawing ability and the importance of the intramolecular hydrogen bond. The calculations suggest that an experimental mixed absorption band at 361 nm could be assigned to MLCT and LLCT transitions. The electron withdrawing nature of the ancillary ligand inC2 explains the electrochemical behavior, which shows the oxidation of Re I at 1.83 V and the reduction ofdeeb at −0.77 V.